Analisis Perbandingan Metode Routing Spray and Wait dengan Prophet untuk Daerah Terpencil - Imron Sazali; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Indonesia's geographical conditions, some of which are inland, in which there is no reliable internet connection. Routing model selection is highly dependent on the geographical conditions of the area. Routing is a process for determining the route from source to destination in a communication scheme. It takes a Routing scheme that has tolerance for delay, mobility, and requires minimal resources. Delay Tolerant Network (DTN) technology is a data delivery mechanism that resists latency, and can carry large data packets with minimal system resources. With the DTN (Delay Tolerant Network) technology the problem is likely to be resolved. Two DTN protocols in this final project are Prophets that use knowledge and Spray and Wait with replica strategies. Both protocols are simulated in a predetermined environment using One Simulator and then analyzed based on performance measurement parameters of delivery probability, average delay and overhead ratio. From the results of research conducted, obtained data that Routing Spray and Wait has a tendency better performance in terms of Delivery Probability and Average Delay. Whereas in the case of Overhead Ratio, Routing Prophet shows a smaller value. For the environment that has characteristics as in this study Spray and Wait is better than Prophet.